Design And Simulation Of A High Thrust Linear Oscillatory Actuator - Khamis, Alias (2007)

(untitled)
An actuator is widely used in many applications either in automation, transportation, productions, robotics, logistics, etc. There are many types of actuator available in the market. An actuator is a device that converts energy into limited mechanical motion. The form of energy could be electric, hydraulic or pneumatic. Electric actuator is much superior compare to other energy form. It gives efficiency, controllability, cost and environmental safety. This thesis is a study on designing a linear oscillatory actuator based on electromagnetic theory. The aim of this study is to develop a linear oscillatory actuator for mechanical cutter with high thrust. Linear oscillatory actuator (LOA) is a type of linear actuator whereby its motion is in single axis and moves continuously. In this research, the design starts from magnetic analysis using Finite Element Method (FEM). This software can simulate the flux density, flux flow, thrust, cogging force, normal force on the element and material in the motor including electromagnet element. The LOA was designed to have a view of its structure before simulate the design by Microcal Origin software. Then, simulation was done to obtain the best thrust, cogging force and normal force value. Few modifications on the structure are done during this simulation to identify the highest thrust, lowest cogging force and normal force. Simulations of all designed modelling are compared. Future recommendation has been provided to help other researcher for further development of this LOA.